Enhancing productivity of kharif onion for Bundelkhand region - Singh, R K; Soni, Shweta; Dwivedi, S V; Mishra, A C; Singh, Ajeet (Indian Horticulture, 2023)
Onion is widely cultivated for internal consumption as well as for the export. India is the major onion-producing country in the world. At regular intervals, onion makes us cry by its high price fluctuations and gap between supply and demand. Therefore, it is high time to take the privilege to divert mass for cultivation of onion in kharif season by using simplest technological interventions. As the climate of Bundelkhand region matches with climate of Deccan plateau where kharif onions are being grown over the years, therefore, we also want to take advantage of ecological boundaries and to disseminate the cultivation at large scale under participatory production programme. As of now, we have already shortlisted the most prominent variety of onion namely, Line-883 from the available pool which matures as early as by 80-82 days and produces 25-30 tonnes of bulb yield under poor resource conditions. These prominent lines/varieties need large dissemination at grass route level. This certainly will change the socio-economic conditions of small and marginal growers and generate employability to the rural landless farmers of the region that can help to restrict seasonal migration of the labours.